Anti-anginal and anti-ischemic effectiveness of trimetazidine MB in patients with unstable angina - M. G. Glezer; S. V. Msilyev (Кардиоваскулярная терапия и профилактика)
Aim. То analyse trimetazidine therapy potential in unstable angina (UA).Material and methods. In a randomised, placebo-controlled study including 50 UA patients, the effects of adding trimetazidine MB to standard therapy on angina attack dynamics, total ST depression and QT duration were evaluated. Clinical outcomes were registered during 6 months of the follow-up.Results. In trimetazidine patients (main group, MG), angina attack number reduced after 7 days of the treatment, as well as 30 days and 6 months later — 2,70±1,06, 0,50±0,09 and 0,7±0,12 per week, respectively, comparing to the control group (CG) receiving standard therapy only — 7,10±0,95 (p<0,05); 5,30±1,14 (p<0,01) and 2,0±0,14 (p<0,01), respectively. Faster reduction in total ST depression was observed in MG: 2 hours later, 1,14±0,2 mm in MG vs. 2,60±0,3 mm in CG; at Day 3, 1,11±0,2 mm vs. 2,09±0,3 mm, respectively; at Day 7, 1,09±0,1 mm vs. 2,03±0,1, respectively; one month later, 0,76±0,1 mm vs. 1,95±0,1 mm (p<0,01). QT duration reduced among MG patients faster than in CG individuals, especially among those with initially increased QT interval. The number of cardiovascular outcomes (myocardial infarction, death, repeated hospitalisation, revascularisation) in 6 months was 8 in MG and 25 in CG (Fishers p=0,0016).Conclusion. The complex UA therapy should include an anti-ischemic medication trimetazidine MB.